BS1 Reprogramming human macrophages with drug X: potential mechanisms for stabilisation of atherosclerotic plaques. (4th June 2021) - Kocsy, Klaudia; Kiss-Toth, Endre; Redgrave, Jessica; Majid, Arshad; Francis, Sheila
Abstract : Introduction: Ischemic stroke is commonly caused by large artery atherosclerosis. Patients with a high atherosclerotic burden (stenosis) and inflamed or ulcerated plaque are at increased risk of early recurrent ischaemic events. Treatment with anti-inflammatory agents may therefore reduce stroke incidence and recurrence in patients with this condition, but in vitro human studies of the possible mechanisms are lacking. We hypothesised that an anti-inflammatory compound (denoted drug X*) alters the expression of macrophage specific genes, including scavenger receptors in in vitro models of human carotid plaque macrophages. Methods: CD14+ monocytes were collected from whole blood donations (volunteers) and differentiated to monocyte derived macrophages (MDMs). Macrophage polarisation with M1 (100 ng/ml LPS + 20 ng/ml INF-γ) and M2a (20 ng/ml IL-4) markers was performed in complete media supplemented with 3 different clinically relevant concentrations of drug X. Gene expression (RT-qPCR) analysis (n=10) was carried out in the differentiated hMDMs to test for macrophage specific genes and scavenger receptors. Western Blot analysis (n=7) and immunofluorescence stain (IF) (n=5) was performed on drug X- treated MDMs to validate changes in the expression of Oxidized Low Density Lipoprotein Receptor 1 (OLR1). The physiological effect of drug X was also tested on oxLDL (25 μg/ml) uptake by macrophages (n=5). Results: Our data suggest that drug X may re-program macrophages to a less inflammatory state (an M2 state) by significantly altering Mannose Receptor C-type 1 (MRC1) gene expression (p:0.0183). Drug X also alters the expression level of Macrophage Scavenger Receptor 1 (MSR1) gene, provoking the pacification of the M1 state and resulting in a beneficial effect on LDL uptake (p: 0.0845). Using OLR1 gene expression as a readout, in both M1 and M2a macrophages, the average OLR1 expression was reduced by treatment with drug X (p: 0.0003). This implies that M1 macrophages can bind less oxLDL which could reduce the formation of atherosclerotic plaque in the vessel wall. OLR1 protein expression was also reduced (p:0.0003) following 24-hour exposure of the macrophages to drug X. In functional tests, oxLDL uptake by drug X treated hMDMs was reduced by 44% (p:0.003). Conclusions: The gene expression of macrophage specific genes and scavenger receptors in human M1 and M2a macrophages was significantly altered following 24-hour exposure to clinically relevant concentrations of drug X in vitro. Drug X reduced 'active' and pathogenic cell behaviours e.g., lipid uptake and promoted the polarisation to the M2 state. These data demonstrate that human macrophages can be reprogrammed to a less pathogenic state in vitro and they provide a potential mechanism for the effectiveness of drug X in the stabilisation of carotid atherosclerotic plaques in humans. * Drug X is used for ongoing IP/patent assessment Conflict of Interest: No